Analysis on SO3 Generation, Migration and Control Technology of Coal-fired Units - Dongxu LIU; Xiaoyuan ZHANG; Qing MA; Qianwei FENG; Zhen DU (Zhongguo dianli, 2024)
In order to analyze the SO3 emission characteristics of coal-fired units, testing the generation and removal of SO3 for the 58 units, analyze the generation of SO3 from combustion in the furnace, the conversion of SO2/SO3 from denitration system, and the removal effect of SO3 for dry dust remover, wet desulfurization system, and wet dust remover, so as to obtain the rule of generation, migration, and removal of SO3 in coal-fired units. The results show that the generation of SO3 in coal-fired units is mainly composed of the combustion of coal sulfur and the conversion of SO2 in the denitration system. The generation rate of SO3 during furnace combustion is approximately 1% of the total amount of SO2 generated during furnace combustion, and the conversion rate of SO2/SO3 in the denitration system is also at 1%. The electrostatic precipitator, electrostatic bag precipitator and wet desulfurization system have limited removal effect on SO3. The removal efficiency of electrostatic precipitator, electrostatic bag precipitator and wet desulfurization system is 15%~25%, 20%~40% and 40%~60%. The low temperature dust remover and wet dust remover have high SO3 removal efficiency. The SO3 removal efficiency of low temperature dust remover is 50%~80%, and that of wet dust remover is 70%~90%. Therefore, the generation of SO3 can be effectively controlled by controlling the sulfur content of coal combustion or the SO2/SO3 conversion rate of the catalyst in the denitration system. At the same time, low temperature dust collectors and wet dust collectors can be used to control the emission of SO3, and SO3 can be controlled below 10mg/m3 through the dry dust collectors, wet desulfurization system, and wet dust collectors.